Fabrication of hafnium-based nanoparticles and nanostructures using picosecond laser ablation - Abhishek Das; Mangababu Akkanaboina; Jagannath Rathod; R. Sai Prasad Goud; Kanaka Ravi Kumar; Raghu C. Reddy; Ratheesh Ravendran; Katia Vutova; S. V. S. Nageswara Rao; Venugopal Rao Soma (Beilstein Journal of Nanotechnology)
This work presents a unique and straightforward method to synthesise hafnium oxide (HfO2) and hafnium carbide (HfC) nanoparticles (NPs) and to fabricate hafnium nanostructures (NSs) on a Hf surface. Ultrafast picosecond laser ablation of the Hf metal target was performed in three different liquid media, namely, deionised water (DW), toluene, and anisole, to fabricate HfO2 and HfC NPs along with Hf NSs. Spherical HfO2 NPs and nanofibres were formed when Hf was ablated in DW. Hf ablated in toluene and anisole demonstrated the formation of core–shell NPs of HfC with a graphitic shell. All NPs exhibited novel optical reflectance properties. Reflectance measurements revealed that the fabricated NPs had a very high and broad optical absorption throughout the UV–vis–NIR range. The NPs synthesised in toluene exhibited the best absorption. The successful fabrication of Hf NSs with the formation of laser-induced periodic surface structures (LIPSS) with low spatial frequency (LSFL) and high spatial frequency (HSFL) orthogonal to each other was also demonstrated. The LSFL and HSFL both exhibited quasi-periodicity. This work presents a simple way to fabricate HfO2 and HfC NPs and provides insight into their morphological and optical characteristics paving way for their applications in future.